PEMASARAN ERA MODERN E-COMMERCE: PENGARUH E-COMMERCE SEBAGAI STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN RIZKY OLSHOP - Rahmadini, Salsa; Arobiansyah, Novaldi; Bastian Rabani, Dimas; Akbar, Raihan; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
Rizky_olshop is an online store that sells thrifted products such as jackets and vests through the Shopee platform. Despite taking advantage of promotional features in the form of video and live streaming, the store still faces challenges in increasing sales. This research uses a qualitative method with a descriptive approach, through the collection of data from various sources, such as books, previous research reports, and semi-structured interviews. The results of the study show that although Rizky_olshop can utilize the Shopee platform as a sales medium, diversifying the marketing platform and applying more varied promotional methods has the potential to improve sales performance. In addition, improving product quality and customer service is also an important factor in building consumer trust and loyalty. With the consistent implementation of these strategies, Rizky_olshop have the opportunity to achieve greater success in the increasingly competitive e-commerce market.